Has the Child Dental Benefits Schedule improved access to dental care for Australian children?. (25th March 2022) - Stormon, Nicole; Do, Loc; Sexton, Christopher
Abstract: The Child Dental Benefits Schedule (CDBS) is an ongoing scheme administered through the Australian Government providing eligible children funding for clinical dental treatment. This study aimed to investigate the access of dental services across children's early childhood and examine whether the CDBS has improved access to dental care. The longitudinal study of Australian children is an ongoing cross‐sequential cohort study with a representative sample of Australian children recruited in 2004. Birth (0–1 year) and kindergarten (4–5 years) cohorts were recruited through Medicare enrolment information at baseline and were representative of the Australian child population. Population‐weighted longitudinal mixed effects Poisson models with individual identifiers as a random effect were used to assess the effect of Medicare dental schedules on reported dental attendance. Prior to the implementation of the CDBS for both cohorts, the birth cohort reported the lowest attendance rate at age 4–5. The introduction of the CDBS increased the rate of dental attendance for the low household income group by 8% (95% CI: 1%, 15%) after adjusting for confounders. The model provides evidence that dental attendance increased with age and the Indigenous population have 31% (95% CI: 4%, 55%) lower attendance rate after adjustment. The increase in reported access to dental services and favourable visiting patterns in low‐income households during the operation of the CDBS provides some evidence that the schedule's primary aims to improve access to care in the child population are being met. Access to healthcare is multifaceted and the underutilisation of the schedule in the population warrants review of the schedule performance using other patient‐centred indicators.